Penguatan Ketrampilan Vokasional Digital Pelajar dan Guru SMA di Kota Bandung - Manurung, Elvy Maria; Ida Nuraida; Nina Septina; Surbakti, Ronny Trian (Journal of Applied Community Engagement, 2023)
The gap between higher education graduates who are ready to use and those accepted to work in the industrial world shows that there is a problem between the link and match between higher education and industry. The Ministry of Education and Culture calls for curriculums that are not in line with industry needs to be corrected. The low competency and skills of graduates become a source of problems with the absorption of higher education graduates. In addition to the acceleration of technology, especially in the field of digitalization which has developed rapidly during the Covid-19 pandemic, it has encouraged the development of Vocational Education as a national issue. The community service carried out by the UNPAR Vocational Program in 2023 is intended to answer these challenges by providing vocational training to several high school and vocational school students and teachers. Through this community service activity, with practical materials such as digital administration offices, entrepreneurship, digital marketing, simple financial recording, and e-sport management; has proven to be able to help students and teachers because it can be implemented immediately. Vocational Education as an alternative to further study in higher education is expected to continue to develop its learning materials and make new breakthroughs or innovation so that its existence can be recognized by the community especially students, parents, and teachers in high school or vocational schools. In this way, the problem of link-match between graduates and workforce qualifications needed in the industry can be more well-connected and appropriate.